Implementasi Kebijakan Publik Melalui Sistem Pelayanan Rakyat Sidoarjo di Desa Medaeng - Slamet Hariyono; Widyawati Widyawati; Nihayatus Sholichah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
In the current era of digitalization, public needs for fast, efficient, and transparent public services are increasing. The Sidoarjo Regency Government responds to these needs by launching a technology-based public service innovation, namely the Sidoarjo People's Service System (SiPraja) application. This study aims to analyze the implementation of public policy through SiPraja in Medaeng Village, Waru District, Sidoarjo Regency. The method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation study. Research informants consisted of the Village Head, village officials, SiPraja operators, and community service users. The results show that the implementation of SiPraja in Medaeng Village has been quite good based on the Van Meter and Van Horn indicators, including the size and objectives of the policy, resources, characteristics of implementing agents, attitudes of implementers, inter-organizational communication, and social, economic, political environments. Supporting factors for implementation include high village government commitment, adequate technology infrastructure availability, and active community participation. However, there are still obstacles in the form of uneven digital literacy among the community, especially in the elderly age group, and limited understanding of some residents regarding application usage procedures. This study provides recommendations to increase the intensity of socialization and training on the use of the SiPraja application, as well as optimize the role of RT/RW as community assistance agents.